Management Control Systems in the Business Sector: Understanding Trends from Selected Literature in an International Setting - Anup Chowdhury; Nikhil Chandra Shil (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
In a business organisation management control systems are found in the design of organisational structures and the policies and procedures used for planning and evaluation. Many authors have defined management control systems in many ways and as a result different typologies of management control have evolved to define management behavior. Management control systems must be expanded to managerial practices that cultivate employee cooperation and creativity in the discovery and exploitation of new business opportunities. This study is an attempt to explore the trends of management control systems applied in different country’s business sector based on worldwide selected published literatures.